An illustrious man and his uomini illustri - Manuali, T; Bastianich, Tanya (2000)
The thesis begins with a cursory discussion of the Classical literary and visual sources for Renaissance uomini illustri cycles. The conveyance of these specific Classical sources to medieval France is touched upon, which leads to the rebirth of the uomini illustri genre in the guise of the chivalric NeufPreux. The discussion of the conceptual and artistic genesis of the uomini illustri genre creates an extensive time line, with some lacuna, that allows us to visualize the development of this theme right up to Renaissance Italy. A synopsis of the many uomini illustri cycles on the Italian peninsula is then given. The significance that the cycles may have embodied in relation to the environment for which they were created, as well as the meaning that they may have held for the viewer and patron is examined. Subsequently, a biography of Francesco di Marco Datini is given, touching on his early sojourn in Avignon, his activities in Italy during the construction and decoration of the Palazzo Datini, as well as his artistic patronage as a whole. Datini's friendships with the foremost humanist thinkers of the time is analyzed. This study, as well as the analysis of Francesco di Marco Datini as a merchant and a man living on the cusp between the Tre and Quattrocento, provides the context in which to visualize the creation of the uomini illustri cycle in Palazzo Datini, although the decoration of the cortile extends beyond simply the representation of historical figures to include virtues, vices, the sciences and philosophers, a trait common in other contemporary uomini illustri cycles. The complicated and diverse stages of the construction and decoration of Palazzo Datini is closely scrutinized, so that together with documentary evidence from the fecund Archivio di Stato di Prato (much of which has not been previously published) a clear reconstruction of the building of the palazzo and its decoration can be given for the first time. I discuss the careers of artists working for Datini, particularly Niccolo v di Piero Gerini, the main artist working on the extended uomini illustri cycle of Palazzo Datini. The final goal is the physical, iconographical, and conceptual reconstruction of the courtyard decoration of Palazzo Datini.